Biomineral Deposition of Magnesium Phosphates: Mixture of Mg3(PO4)2·22H2O and KMgPO4·6H2O - Yu, Xiaoniu; Qian, Chunxiang; Wang, Xin (Asian Journal of Chemistry, 2014)
The magnesium phosphates which are the mixture of Mg3(PO4)2·22H2O and KMgPO4·6H2O was prepared by microbiological method. The main process is substrate hydrolysis by the alkaline phosphatase produced by phosphate-mineralization microbe, in Mg2+ and K+ environment. The structural characterization by X-ray techniques, energy dispersive X-ray spectroscopy and morphological observations via scanning electron microscope showed that the irregular shape of magnesium phosphates have been prepared. And biomineralizing mechanism showed that bacterial body and metabolites play important roles in the process of crystal nucleation, growth and accumulation of magnesium phosphates.